2010
DOI: 10.1007/s11274-010-0639-5
|View full text |Cite
|
Sign up to set email alerts
|

Impact of delay in processing on mold development, ochratoxin-A and cup quality in arabica and robusta coffee

Abstract: Delay between harvesting of coffee berries and onset of processing are common in most of the coffeeproducing countries worldwide. Delay in processing is considered to be a negative operation in coffee production with respect to quality and safety. The aim of this study was to reconfirm the impact of delay in processing on ochratoxin A contamination in coffee and subsequent coffee quality. Delay in processing was found to favor higher mold incidence in cherry as compared to parchment coffee of both arabica and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Studies on the mycobiota of coffee cherries and beans have demonstrated that the toxigenic fungal genera Aspergillus and Penicillium are the predominant contaminants (Viegas et al., 2017) and that the Aspergillus genus is the most common contaminant, its presence in coffee being widely reported (Morgan et al., 2018; Noonim et al., 2008; Oliveira et al., 2019). The presence of fungal contamination causes defects in the physical and organoleptic characteristics of coffee beans, decreasing cup quality (Velmourougane et al., 2011). OTA is mainly produced by certain fungal species from the genera Aspergillus and Penicillium .…”
Section: Resultsmentioning
confidence: 99%
“…Studies on the mycobiota of coffee cherries and beans have demonstrated that the toxigenic fungal genera Aspergillus and Penicillium are the predominant contaminants (Viegas et al., 2017) and that the Aspergillus genus is the most common contaminant, its presence in coffee being widely reported (Morgan et al., 2018; Noonim et al., 2008; Oliveira et al., 2019). The presence of fungal contamination causes defects in the physical and organoleptic characteristics of coffee beans, decreasing cup quality (Velmourougane et al., 2011). OTA is mainly produced by certain fungal species from the genera Aspergillus and Penicillium .…”
Section: Resultsmentioning
confidence: 99%
“…The occurrence and activity of specific microbial groups can be associated with diverse functionalities during processing, for instance, the degradation of pulp pectin and the depletion of mucilage carbohydrates (5-7, 12, 23). Their metabolite production capacities can have beneficial and/or detrimental effects on the sensory characteristics of the green coffee beans and final coffee cup quality (3,(24)(25)(26). However, it is not yet clear to what extent microorganisms are essential for the production of high-quality coffee (2).…”
mentioning
confidence: 99%
“…A study of the microbiota associated with the semi-dry process [13] revealed that normally in the early stages of the fermentation bacteria prevail, while in the later stages the yeasts are predominant, simultaneously with the decreasing of the moisture content. Delays during the semi-dry fermentation and drying process can trigger the outgrowth of filamentous fungi, potentially leading to food safety risk and decreased beverage quality [45]. Yeasts have an essential role in preventing oxygenic filamentous fungi growth and boosting the production of pectinolytic enzymes, which helps the degradation of coffee mucilage and pulp [18].…”
Section: Role Of Yeasts In Controlling the Production Of Non-desired mentioning
confidence: 99%